Caliphaea sinuofurcata sp. nov. (Odonata: Zygoptera: Calopterygidae) from Arunachal Pradesh, India - Sawant, Dattaprasad; Joshi, Shantanu; Pawar, Ujwala; Nawge, Viraj; Kunte, Krushnamegh (Zootaxa, 2025)
We describe a new species, Caliphaea sinuofurcata sp. nov., based on two male and one female specimens collected from Upper Siang District and Lower Dibang Valley District, Arunachal Pradesh, India. The newly described species can be distinguished from its congeners by characteristic shape of paraproct and genital ligula. Additionally, we provide illustrations of the male caudal appendages for all known Caliphaea spp.